Peran Koperasi Simpan Pinjam Pinang Mandiri dalam Pengembangan Usaha Mikro Kecil dan Menengah di Desa Teluk Pinang (Berdasarkan Prinsip Ekonomi Islam) - Nurmayanti, Nurmayanti; Asri, Kholifatul Husna; Yanto, Riadi (Innovative: Journal Of Social Science Research, 2025)
In order to create implementation of regional autonomy policies, especially in improving savings and loan cooperatives, of course we must empower micro, small and medium enterprises which are of particular concern in this use. With that, researchers are interested in knowing and explaining the role of the Pinang Mandiri Savings and Loans Cooperative in the development of Micro, Small and Medium Enterprises in Teluk Pinang Village and to find out whether the cooperative applies Islamic economic principles or not. This research uses descriptive qualitative methods through observation, interviews and documentation. This research involved 6 resource persons, consisting of 6 Micro, Small and Medium Enterprise entrepreneurs in Teluk Pinang Village. The results of this research are: 1). The role of the Pinang Mandiri savings and loan cooperative as a provider of business capital. Savings and Loans Cooperatives provide easy access to sources of financing for Micro, Small and Medium Enterprises who often have difficulty getting loans from formal financial institutions such as banks. The loan process at Savings and Loans Cooperatives is usually simpler and more flexible. 2) The role of Savings and Loans Cooperatives can also reduce dependence on moneylenders. With the presence of Savings and Loans Cooperatives, Micro, Small and Medium Enterprises do not need to depend on moneylenders who often charge high interest rates which are strictly prohibited in Islamic teachings. Pinang Mandiri Savings and Loans Cooperative offers friendlier and fairer interest rates.